Performance of the ABC-bleeding risk score for assessing major bleeding risk in Chinese patients with atrial fibrillation on oral anticoagulation therapy: A real-world study - Wang, Yu-Feng; Jiang, Chao; He, Liu; Pu, Cun-Ying; Du, Xin; Sang, Cai-Hua; Long, De-Yong; Tang, Ri-Bo; Dong, Jian-Zeng; Ma, Chang-Sheng (Frontiers in Cardiovascular Medicine, 2022)
Objective: To evaluate performance of the ABC (Age, Biomarkers, Clinical history)-bleeding risk score in estimating major bleeding risk in Chinese patients with atrial fibrillation (AF) on oral anticoagulation (OAC) therapy in real-world practice. Methods: Data were collected from the Chinese Atrial Fibrillation Registry study (CAFR). Patients were stratified into low-, medium-, and high-risk groups based on ABC-bleeding risk score with 1-year major bleeding risk (<1%, 1-2%, and >2%) and modified HAS-BLED score (≤1,2 and >2 points). Cox proportional-hazards (Cox-PH) models were used to determine the association of major bleeding incidence with bleeding scores. Harrell’s C-index and net reclassification improvement (NRI) of the two scores were compared. Results: The study included 2,892 AF patients on OAC therapy. After the follow-up of 3.0 years, 48 patients had major bleeding events; the incidence of a bleeding event in the low-, medium-, and high-risk groups according to ABC-bleeding risk score was 0.31% (reference group, HR=1.00),0.51% (HR=1.83, 95%CI: 0.91-3.69, P=0.09), and 1.49% (HR=4.92, 95%CI: 2.34-10.30, P<0.001), respectively. Major bleeding incidence had an independent association with growth differentiation factor 15 (GDF-15) level (HR=2.16, 95%CI: 1.27-3.68, P=0.005) after adjusting components of the HAS-BLED score and cTnT-hs level. The ABC-bleeding score showed a Harrell’s C-index of 0.67 (95%CI: 0.60-0.75) in estimating major bleeding risk, which was non-significant compared to the modified HAS-BLED score (0.67 vs. 0.63; P=0.38). The non-significance between the predictive performance of the two scores was further revealed by the NRI (5.23%, P=0.67). Cross-tabulation of the two scores showed that the ABC-bleeding score outperformed the HAS-BLED score in identifying patients with a high risk of major bleeding. Conclusions: This study verified the value of the ABC-bleeding risk score in assessing major bleeding risk in Chinese patients with AF on OAC therapy in real-world practice and suggests that this score performed better in stratifying patients with a high risk than the modified HAS-BLED score. Combining the two scores could be a clinically practical strategy for precisely stratifying AF patients, especially those at a high risk of major bleeding, and further supporting the optimization of OAC treatment.